Evaluasi Pengakuan Pendapatan Premi dalam Kaitannya dengan Penyajian Laporan Laba Rugi secara Syariah Studi Kasus pada PT. Takaful Indonesia - Divisi Asuransi Takaful Keluarga - Budianto, Enjang Tachyan; Sumiati, Mia (Jurnal Ilmiah Ranggagading (JIR), 2009)
Takaful Insurance is an insurance based on syariah of Islam. Takaful Insurance forms risk classified arrangement meeting needs. In carrying out its activities, PT Asuransi Takaful Keluarga operates on profit sharing concepts (mudharabah). The accounting policy is arranged based on syariah of Islam policy where premium revenue has influence towards presentation of balance. Therefore, if there is fault in implementing premium revenue recognition, it will result in profit and loss account (presentation of balance) yielded is not accurate and it will issue misinformation to information users. The goal of this research is to evaluate premium revenue recognition in accordance with presentation of balance. The result of this research shows that PT Asuransi Takaful Keluarga has recognized premium revenue in accordance with the instruction of National Syariah Bord No. 19, 2001. Finance account of PT. Takaful has been audited by KAP (Kantor Akuntan Publik or Public Accountant Firms) Mulyamin Sensi Suryanto with proper opinion without making an exception (unqualified opinion). Keywords : Premium Revenue Recognition; Presentation of Balance